Ensuring Sustainability: Leadership Approach Model for Tackling Procurement Challenges in Bulgarian Higher Education Institutions - Mina Daskalova-Karakasheva; Denitza Zgureva-Filipova; Kalin Filipov; George Venkov (Administrative Sciences)
At present, higher education institutions (HEIs) are increasingly expected to incorporate sustainability into all aspects by integrating it not only into education and research but also into operational processes, including procurement. In some cases, national legislation hinders public universities from adhering to sustainability requirements. This paper aims to introduce a leadership approach model that enables public universities to overcome the constraints imposed by the legal framework. To explore the relatively new area of Sustainable Public Procurement (SPP), where still little is known, the Technical University of Sofia (TU-Sofia) was chosen as a testbed for the case study. Firstly, the challenges posed by external factors—such as non-discrimination principles stated in Bulgaria’s Public Procurement Act (PPA) and internal incentives at TU-Sofia for sustainable procurement initiatives were identified. Secondly, based on the findings, the recommendation is to adopt a leadership approach model by developing and implementing a Sustainable Public Procurement Policy (SPPP) tailored to harness the university’s sustainable development drivers while complying with legislative requirements. As a result of the leadership approach model implementation, the university will not only enhance economic benefits but also mitigate risks and drive transformative change in procurement management processes, contributing to broader societal and environmental goals.